Modelling and optimisation of tongkat ali water extract production utilising a batch process simulator - Athimulam, Arunasalam; Kumaresan, Sivakumar; Foo, Dominic Chwan Yee; Sarmidi, Mohamad Roji; Abdul Aziz, Ramlan (2005)
Eurycoma longifolia or Tongkat Ali water extract is a valued product in the phytochemical industry. This work features the modelling and optimisation of a Tongkat Ali water extract production using SuperPro DesignerÂ®, a batch process simulator. The objective of this work is to design an economically viable production scheme for a locally developed Tongkat Ali extract production process. The current pilot scale production scheme of Tongkat Ali extract was used to simulate the base case process. Four alternative production schemes were further developed with several debottlenecking and optimisation strategies. The final alternative scheme was reported to achieve a product yield of 3.00%, with an annual production of 1137.72 kg of Tongkat Ali extract. The minimum batch cycle time was reduced from 24.4 hours in the base case to 8.04 hours. Economic analysis determined that the proposed alternative production scheme has an annual revenue of $6.32M, with a 38.6% gross margin and a 32.9% return on investment.